2003
DOI: 10.1016/s0022-2836(02)01449-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Krüppel-like Factor 4 Reveals a Function in Cell Cycle Regulation and Epithelial Differentiation

Abstract: Krüppel-like factor 4 (KLF4) is an epithelially enriched, zinc finger-containing transcription factor, the expression of which is associated with growth arrest. Constitutive expression of KLF4 inhibits G1/S transition of the cell cycle but the manner by which it accomplishes this effect is unclear. To better understand the biochemical function of KLF4, we identified its target genes using cDNA microarray analysis in an established human cell line containing inducible KLF4. RNA extracted from induced and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 89 publications
15
162
0
Order By: Relevance
“…Remarkably, KLF4 had opposing effects on the cyclin-dependent kinase inhibitor p21 CIP1 and on p53. First, KLF4 expression led to an increase in p21 CIP1 levels (a finding that corresponds with previously reported data 3,6 ; Fig. 2a), which occurred independently of p53 (Fig.…”
Section: Klf4 Suppresses P53 But Induces P21 Cip1supporting
confidence: 90%
“…Remarkably, KLF4 had opposing effects on the cyclin-dependent kinase inhibitor p21 CIP1 and on p53. First, KLF4 expression led to an increase in p21 CIP1 levels (a finding that corresponds with previously reported data 3,6 ; Fig. 2a), which occurred independently of p53 (Fig.…”
Section: Klf4 Suppresses P53 But Induces P21 Cip1supporting
confidence: 90%
“…KLF4 accomplishes this task both through its transcriptional activation of p21 WAF1/Cip1 and through direct suppression of cyclin D1 [19] and cyclin B1 expression [18], which are required for the G 1 /S and G 2 /M transitions, respectively. Expression profiling of KLF4 using cDNA microarray analysis confirmed that KLF4 activates transcription of many additional genes encoding inhibitors of the cell cycle and suppresses those encoding promoters of the cell cycle [20]. Recent studies from our laboratory indicate that KLF4 is also involved in preventing centrosome amplification after γ irradiation [21] and possibly in preventing aneuploidy after spindle damage (Dalton and Yang, unpublished observations).…”
Section: Klf4 and 5 Exhibit Contrasting Effects On Cellular Proliferamentioning
confidence: 69%
“…KLF4 then exerts a multitude of effects on expression of downstream genes by activating ( ) or inhibiting their expression ( ). References in support of the specific pathways are as follows: p53 KLF4 p21 [16]; KLF4 cyclin D/Cdk4 [19]; KLF4 cyclin B/Cdc2 [18]; KLF4 cyclin E/Cdk2 [21]; KLF4 STK15 [20]; KLF4 14-3-3 σ ; KLF4 BUB1/MAD2 [20].…”
Section: Klf4 and Klf5 Exert Distinct Physiologic Functions In Vivo Amentioning
confidence: 99%
See 1 more Smart Citation
“…What are these activities, and how are they regulated by KLF4? CDKN1A, are involved in differentiation and cell-cycle inhibition 28 (TABLE 1). Klf4-knockout mice show defects in skin differentiation 29 as well as a reduced number of secretory goblet cells in the colon 30 , indicating that KLF4 functions as a proliferation-differentiation switch.…”
mentioning
confidence: 99%